Sports and soft tissue injuries a guide for students and therapists - Norris, Christopher M. (Routledge, Taylor & Francis Group, 2019)
It is an important text for students of sports therapy, physiotherapy, sport medicine and athletic training, interesting further reading for sport and exercise science or kinesiology students with an interest in sports injury, and a crucial reference for practising physiotherapists and athletic trainers and the related disciplines.